White-collar crime : a systems approach - Payne, Brian K. (Los Angeles : SAGE, 2022)
"White Collar Crime third edition is a comprehensive introduction to the most important topics students need to know about white-collar crime. Taking a systems approach that examines the many facets of white-collar crime by focusing on different crimes as well as the various systems that are given the task of responding to white-collar misconduct, Brian K. Payne provides a theoretical framework and context for students to explore white-collar crime as a crime problem, a criminal justice problem, and a social problem. Key points help keep the reader focused on the most important information In Focus box inserts bring the concepts to life and help readers contextualize what they are learning Discussion questions allow for further examination and critical thinking in and out of the classroom Recent examples of white-collar crimes are included with specific consideration given to those cases that would be most interesting to students"--
Includes bibliographical references (pages 492-548) and index.
Keywords: White collar crimes; Commercial crimes; Employee theft; Shoplifting